2020
DOI: 10.34218/ijmet.11.10.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Coating Thickness, Hardness and Wear Resistance of Aluminum 6061 by Anodizing Treatment

Abstract: Aluminum 6061 has the advantages such as good formability, corrosion resistance and lightweight, but it also has weaknesses, such as its hardness andwear resistance are relatively low, thus anodizing process is conducted to increase its hardness and wear resistance. The anodizing process can also produce a more attractive appearance and texture of metal. It alsocan increase the resistance of surface friction. The anodizing technique isa metal plating processbased on the formation of an aluminum oxide coating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The thickness of the oxide layer without bio-additive was about 13 μm. It was reported that the thickness of the alumina layer manufactured in the sulfuric acid bath with the applied voltage of 30 V and 30 min was about 6 μm [23]. Although, the thickness range for alumina layers was about 2-7 μm at relatively high temperatures (33 °C-35 °C) [24].…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of the oxide layer without bio-additive was about 13 μm. It was reported that the thickness of the alumina layer manufactured in the sulfuric acid bath with the applied voltage of 30 V and 30 min was about 6 μm [23]. Although, the thickness range for alumina layers was about 2-7 μm at relatively high temperatures (33 °C-35 °C) [24].…”
Section: Resultsmentioning
confidence: 99%
“…The greater the pressure the greater the wear impact generated by the detachment of metal layer and cracks generated by these higher loads (Kamalpreet and Pandey, 2013). Suryo et al (2018) study the wear and corrosion of track shoe of the undercarriage. The shoe is shown in Figure 1.…”
Section: Metal Wearmentioning
confidence: 99%
“…Detektor menangkap elektron sekunder dan menghasilkan tanda elektronik. Sinyal ini diperkuat dan diubah menjadi gambar pindaian video yang dapat diamati pada monitor atau ke gambar digital yang dapat dikumpulkan dan diolah lebih lanjut [14].…”
Section: Gambar 5 Proses Anodisasiunclassified